Electronic and Optical Properties of Sodium Niobate: A Density Functional Theory Study - Daniel Fritsch (Advances in Materials Science and Engineering)
In recent years, much effort has been devoted to replace the most commonly used piezoelectric ceramic lead zirconate titanate Pb[ZrxTi1−x]O3 (PZT) with a suitable lead-free alternative for memory or piezoelectric applications. One possible alternative to PZT is sodium niobate as it exhibits electrical and mechanical properties that make it an interesting material for technological applications. The high-temperature simple cubic perovskite structure undergoes a series of structural phase transitions with decreasing temperature. However, particularly the phases at room temperature and below are not yet fully characterised and understood. Here, we perform density functional theory calculations for the possible phases at room temperature and below and report on the structural, electronic, and optical properties of the different phases in comparison to experimental findings.